A prática de registro dos terapeutas ocupacionais na educação inclusiva - Bombarda, Tatiana Barbieri (Universidade Federal de São Carlos, 2014)
The participation of occupational therapists in inclusive education has been constituted as a field in progress in the country with intervention not only focused in the student, but extended to the school, teachers, classmates and family. The records of these interventions are as important as understanding the practices developed, since this procedure is a fundamental part of the work. Considering that there is no standard methods to document the services of occupational therapy, it is necessary to pay attention to the fact that regardless of the method, the action of the record comes from the need to have information deriving from the assistance as a way of orientation and follow up inspection over the service provided and about the technical responsibility adopted, and being also a supplier source for research data. Glimpsing the importance of documentation, this study was aimed to identify, according to the opinion of the occupational therapists in the state of São Paulo who work in inclusive education, how the records of their interventional practices are performed. Methodologically a questionnaire was provided in a specific web site during a predetermined period and the obtained data were analyzed using descriptive statistics. The participants were 55 occupational therapists who work in the process of inclusive education and registered in the 3rd Region of the Regional Council of Physical Therapy and Occupational Therapy. The results show that the free narrative style can be considered the most used model in registering information, with responses (35.7 %) affirming that there is not the practice of recording all interventions. The lack of availability of time for the records within the routine work was also indicated by 60.7 % of the participants. Over half of the interviewed mentioned that the school institution had received some form of intervention from another occupational therapist, where 80.6% of the cases have documentation about this work, and 48 % of these notes were indicated by participants as not containing sufficient information to understanding and continuance. It is believed that this study allowed views of praxis, signaling new points to be investigated, which consequently, could contribute to improvements in the quality of records and also in the improvement of the profession.
The practice of record of the occupational therapists in the inclusive education
Keywords: Educação inclusiva; Registros; Documentação; Records; Documentation; Occupational therapy; Inclusive education; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL